(untitled) (Research, Society and Development, 2022)
To compare the effects of photobiomodulation with and without laser exposure at wavelengths 660 nm and 808nm in post-surgical wounds, as to its efficacy in the aspects of biostimulation, analgesia, anti-inflammatory. Methodology: The sample consisted of 20 patients requiring extraction in different arcades, totaling 20 extractions. The population was inserted in two groups, A and B in which one of the groups was applied to laser therapy and the other group without the application of laser therapy, according to a pre-established protocol and with the knowledge of patients to the procedures to be performed. Also applied a visual analog scale (VAS) and numerical visual scale (EVN) to record the degree of analgesia of these patients. Results: The results showed a decrease in painful symptomatology for the experimental group and a satisfactory postoperative period. Final Considerations: Laser for therapeutic purposes is an easy-to-handle and well-feasible tool in the routine of dental clinics. It can be used to control postoperative pain in exodontia.